Green Proposal: aspects of sustainability in a small carpentry that uses demolition wood - Sampaio, Cláudio Pereira de (2011)
This article presents results of a study that proposes the use of the concept of eco-efficiency in the productive system of a small carpentry shop, which uses the demolition wood as raw material. For this, the article discusses the concepts of ecoffiency, Cleaner Production (CP) and ecodesign. The methodological approach includes the case study, by using data collection and analysis tools as direct observation, photographic and filmographic registration of the production process, interviews with the company workers and production process mapping. Because of its implementation, the expected benefits are mainly concerned to environmental and economical dimensions of sustainability.